Optimizing The Design Of The KVLCC2 Rudder Using CFD To Reduce The Effect Of The Cavitation - ميهوب غيث (Latakia University Journal -Engineering Sciences Series, 2025)
The rudder of the KVLCC2 tanker ship has a lifting wing section NACA0018, and accordingly, in this research, the effect of the geometric parameters of the rudder on the formation of cavitation around it was studied and analyzed, and then the shape of the rudder was modified to reduce cavitation around it. The URANS equations (Unsteady RANS Averaged Navier Stocks Equation) and the k-Ꞷ SST turbulence model available within the Ansys program were used to solve the Navier-Stokes equations. Cavitation was initially calculated for a benchmark case using CFD in order to ensure the accuracy of the numerical results compared to the available experimental results. The comparison confirmed the accuracy of CFD in predicting cavitation. After that, the effect of the geometric parameters of the rudder on the cavitation formed around the rudder with and without rudder drift angles and at different values ​​of the cavitation number and Froude number was studied. Then, the shape of the rudder was modified to reduce the possibility of cavitation occurring, and it was retested again at different values ​​of the drift angles and the cavitation number. The results obtained confirmed that dividing the rudder into two symmetrical, independently controllable parts and deflecting only one part of the rudder significantly reduces the cavitation formed on the rudder surface.